Blood conservation in total joint surgery a multimedia program for orthopedic surgeons - Healy, William L.; GWF Associates (Hamilton : GWF Associates, 1999)
Explore various techniques to conserve blood and minimize allogeneic transfusions in patients undergoing total hip and knee replacements
Approved for up to 8 hr. of CME credit in category 1 toward the AMA Physician's Recognition Award
System requirements: Pentium 166 MHz; 24 MB RAM; Windows minimum configuration, Windows 95, 98, or NT 4.0; display 16 bit col. or more; CD-ROM (4x or faster) or DVD drive; sd. blaster-compatible sd. card 4
System requirements: Macintosh minimum configuration, PowerPC; 24 MB RAM; operating system 7.1 or later; display thousands of colors or more; CD-ROM (4x or faster) or DVD drive
Keywords: Arthroplasty, Replacement; Blood Transfusion; Hemostasis, Surgical